Pandemic Fatigue: A Concept Analysis - Elvira Costa; Catherine Macatangay; Neil Balubar; Roison Andro Narvaez (Health Notions, 2022)
Aim: This concept analysis aims to impart knowledge and recognize the pandemic fatigue of healthcare professional, especially nurses. The concept aims to identify the causes of pandemic fatigue to nurses, especially during the COVID-19 crisis. It also identifies the effect of pandemic fatigue on their productivity, their mental and physical aspect. It also analyzed the definitions of the concept via various case studies and researches like giving examples of the model, related, contrary and borderline cases. Background: Pandemic fatigue is a foreseeable result of an extended health crisis. The gravity of its impact on people's lives and the seriousness of the disease signaled different measures to combat the infection. The pandemic fatigue can be seen from the records of various countries’ growing numbers of individuals who do not adequately conform to given measures, are not aware of the COVID-19 disease, and their exhaustion of the changing safety protocols. Design: Avant and Walker (2019) method of concept analysis. Result: The study has uncovered seven significant contributing attributes of pandemic fatigue, especially healthcare workers, such as exposure to infection, restriction, mortality, relationships with coworkers,  employers and public, PPE/supplies, and nursing shortage mental health. Pandemic fatigue among nurses has been rampant and has affected the healthcare workforce’s daily routine. Prolonged crisis has set the government in a pinch and different hospitals in both private and public. Conclusion: Nurses are prone to developing pandemic fatigue due to their nature of work and the additional burden COVID-19 has brought. Pandemic fatigue can be prevented initially by studying fatigue's underlying cause and formulating strategies to help nurses overcome pandemic fatigue. It can be prevented by following the established guidelines and support from the family and the nurses’ institution. Furthermore, the nurse can develop their behavior on what is suitable for them to control fatigue. Keywords: pandemic fatigue; COVID-19; nursing; concept analysis; Avant and Walker